Hasil Implementasi Pembelajaran Program Tahfiz Al-Qur’an di Pondok Pesantren Tahfizhul Qur’an Al-Imam Ashim Makassar - Rahman, Muh. Akbar; Abubakar, Achmad; Harun, Hamzah; Supardin, Supardin (Jurnal Diskursus Islam, 2023)
This research aims to determine the results of the implementation of the tahfiz al-Qur'an learning program at the tahfizhul Qur'an al-Imam Ashim Makassar Islamic boarding school. This type of research is classified as qualitative with the research approach used being a theological-normative and pedagogical approach. The data sources in this research are foundation administrators and teachers in the tahfiz al-Qur'an program. Furthermore, the data collection methods used are observation, interviews, documentation and reference tracking. Then, data processing and analysis techniques are carried out through three stages, namely data reduction, data presentation, and drawing conclusions. The results of this research show that the implementation of the Al-Qur'an learning program is said to be good based on the various achievements and graduation activities that have been achieved and participated in by the students of the Al-Qur'an Tahfiz program. To the leadership and supervisors of the Tahfizhul Qur'an Al-Imam Ashim Makassar Islamic Boarding School to continuously encourage and contribute to developing the learning system in terms of concepts and providing intensive supervision. To teachers and teachers of the Koran to continue to innovate and develop various models and learning strategies in teaching the Koran, so that students can adapt models that suit their talents and abilities. Students should always maintain istiqamah in good behavior, especially regarding ethics and manners regarding learning the Koran. Abstrak Penelitian ini bertujuan untuk hasil implementasi pembelajaran program tahfiz al-Qur’an di pondok pesantren tahfizhul Qur’an al-Imam Ashim Makassar. Jenis penelitian ini tergolong kualitatif dengan pendekatan penelitian yang digunakan adalah teologi-normatif dan pendekatan paedagogik. Adapun sumber data dalam penelitian ini adalah pengurus yayasan dan juga guru-guru pada program tahfiz al-Qur’an. Selanjutnya metode pengumpulan data yang digunakan adalah observasi, wawancara, dokumentasi, dan penelusuran referensi. Lalu, teknik pengolahan dan analisis data dilakukan melalui tiga tahapan, yakni reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa implementasi pembelajaran program al-Qur’an dapat dikatakan baik berdasarkan berbagai prestasi dan kegiatan wisuda yang diraih dan diikuti oleh para santri program tahfiz al-Qur’an. Kepada pimpinan dan para pengawas Pondok Pesantrean Tahfizhul Qur’an Al-Imam Ashim Makassar untuk terus-menerus mendorong dan memberikan kontribusi dalam mengembangkan sistem pembelajaran dari segi konsep dan memberikan pengawasan yang intensif. Kepada guru dan pengajar al-Qur’an untuk terus berinovasi dan mengembangkan berbagai macam model dan strategi pembelajaran dalam mengajarkan al-Qur’an, sehingga para santri dapat menyesuaikan model yang sesuai dengan bakat dan kemampuan mereka. Bagi santri hendaknya selalu menjaga keistiqamahan dalam berperilaku baik khususnya kepada etika dan adab terhadap pembelajaran al-Qur’an.